2021
DOI: 10.21037/mhealth-20-123
|View full text |Cite
|
Sign up to set email alerts
|

mHealth in hyper-connected Hong Kong: examining attitudes and access to mobile devices and health information among older Chinese residents

Abstract: Background: Hong Kong Special Administrative Region is one of the most technologically advanced and interconnected cities in the world in terms of ownership of internet-enabled mobile devices. mHealth programs that make use of mobile devices such as smart phones and tablets to maximise access to health information, have been identified as having great potential for ageing communities for the management of health and social care needs. This paper reports the findings of a two-stage exploratory research project … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Moreover, the synthesis illustrated how the factors can interrelate with other factors which could further decrease or increase the likelihood of using communicative e-health services. The factors identi ed in the current review support similar ndings from previous literature within the area of older adults and e-health services, such as chronic illness (17)(18)(19), the interface and design (11)(12)(13), poor digital skills (9,16,(19)(20)(21), and a lack of understanding or concern regarding privacy and security online (8, 13,15,16). Additionally, facilitating factors highlighted within the current review corroborate previous literature ndings, such as having support networks (9,(22)(23)(24)(25), recommendations by healthcare providers (26), and having access to technology and the internet (10,27).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the synthesis illustrated how the factors can interrelate with other factors which could further decrease or increase the likelihood of using communicative e-health services. The factors identi ed in the current review support similar ndings from previous literature within the area of older adults and e-health services, such as chronic illness (17)(18)(19), the interface and design (11)(12)(13), poor digital skills (9,16,(19)(20)(21), and a lack of understanding or concern regarding privacy and security online (8, 13,15,16). Additionally, facilitating factors highlighted within the current review corroborate previous literature ndings, such as having support networks (9,(22)(23)(24)(25), recommendations by healthcare providers (26), and having access to technology and the internet (10,27).…”
Section: Discussionsupporting
confidence: 81%
“…Over the years, there has been a growing body of literature focusing on e-health services and older adults (8-10). There are several common barriers and facilitators to e-health services that have been identi ed and these include but are not limited to: poorly designed interface (11)(12)(13), high cost of technology (14), privacy and security issues (8, 13,15,16), chronic illness (17)(18)(19) and lack of digital skills (9,16,(19)(20)(21).…”
mentioning
confidence: 99%
“…First, enough family doctors could provide medical services by going to older adults' homes immediately when they are in need. Meanwhile, related studies recommended that all efforts be expended to extend appropriate rehabilitation services, including home-based care and appliances to those identified as having a disability, particularly to those older than 65 years ( 43 , 55 ). And the services need to be affordable and accessible in terms of suitable transport so that older adults with low income and mobility problems could enjoy these services ( 43 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the positive effects of eHealth literacy on health among the general population. However, older adults face unique challenges when using the internet, such as poor eyesight and limited mobility, which may affect their interest in using the internet and reduce the frequency of internet use [23]. Moreover, most older adults use the internet to socialize and get news, instead of obtaining health information.…”
Section: Introductionmentioning
confidence: 99%